Rabies Prevention Practices Among Dog Owners in Mumias Sub-County, Kakamega County Kenya - Ochieng, Mwima Christoper (Amref International University, 2024)
Introduction: Rabies has a total case mortality rate once clinical signs appear; therefore, it is regarded as a zoonotic illness that poses significant concerns for public health. Domesticated dogs function as the principal carrier for the transmission of rabies. Human rabies has been prevalent in Kakamega County for many years, and the population of stray dogs keeps on increasing due to the presence of a dog market in the area. This study was designed to determine rabies prevention practices among dog owners in Mumias sub-county, Kakamega County, Kenya. Methodology: An analytical cross-sectional design was used, and a sample size 385 was achieved using Fischer’s formula. At each stage of the study, participants were recruited through a random sampling procedure, and data was collected using structured questionnaires. Results: The majority (41.8%) of the sample population had a moderate level of knowledge of rabies prevention practices. Dog confinement methods (65.7%), vaccination services (44.2%), and treatment methods (85.7%) were revealed as common rabies prevention practices. Further, the study found an association between having a formal education, employment status, availability of veterinary personnel in the area (P 0.05), the availability of vaccination points in the dog market (P 0.01) and having a vaccinated dog. Conclusion: Mumias sub-county residents have a moderate level of knowledge of rabies prevention practices. Mumias sub-county residents use dog confinement methods, vaccination services, and treatment methods as preventative measures. Demographic characteristics, preventive measures, the presence of a dog market in the region, and accessibility of veterinary personnel, were factors associated with compliance with rabies prevention practices among dog owners in the Mumias Sub- County Kakamega County Kenya. Recommendations: Increase rabies awareness; Prevention, and dog population control programs, provide dog vaccination points in dog markets as well as formulate policies on unvaccinated dog trade and trafficking.
Keywords: Prevention,Rabies